2017
DOI: 10.1074/jbc.m116.758987
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Insulin Receptor Substrate 1 during Hyperglycemia Induces Vascular Smooth Muscle Cell Dedifferentiation

Abstract: Edited by Jeffrey E. PessinDiabetes is a major risk factor for the development of atherosclerosis, but the mechanism by which hyperglycemia accelerates lesion development is not well defined. Insulin and insulinlike growth factor I (IGF-I) signal through the scaffold protein insulin receptor substrate 1 (IRS-1). In diabetes, IRS-1 is downregulated, and cells become resistant to insulin. Under these conditions, the IGF-I receptor signals through an alternate scaffold protein, SHPS-1, resulting in pathophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Previous work shows that VSMC dedifferentiation is associated with enhanced expression of the transcription factor KLF4 (11) and that enhanced KLF4 expression, which occurs in response to cytokine-induced stress, suppresses transcription of the primary determinant of VSMC differentiation, myocardin (11,12). We demonstrated that KLF4 expression increased in arteries of diabetic or normoglycemic IRS-1 Ϫ/Ϫ mice, and myocardin was suppressed (10). Although the results showed that IRS-1 was required for myocardin expression and differentiation, they did not delineate the mechanism by which maintenance of IRS-1 expression enhances differentiation and inhibits dedifferentiation.…”
mentioning
confidence: 53%
See 4 more Smart Citations
“…Previous work shows that VSMC dedifferentiation is associated with enhanced expression of the transcription factor KLF4 (11) and that enhanced KLF4 expression, which occurs in response to cytokine-induced stress, suppresses transcription of the primary determinant of VSMC differentiation, myocardin (11,12). We demonstrated that KLF4 expression increased in arteries of diabetic or normoglycemic IRS-1 Ϫ/Ϫ mice, and myocardin was suppressed (10). Although the results showed that IRS-1 was required for myocardin expression and differentiation, they did not delineate the mechanism by which maintenance of IRS-1 expression enhances differentiation and inhibits dedifferentiation.…”
mentioning
confidence: 53%
“…This reduction is due to enhanced IRS-1 serine phosphorylation and increased ubiquitination that targets it to a proteasome (22). Recently, we reported that down-regulation of IRS-1 in the arteries of diabetic mice was accompanied by the enhanced expression of KLF4, a transcription factor that enhances VSMC dedifferentiation under certain conditions (10). KLF4 suppressed expression of myocardin, a transcription factor that is required to maintain VSMC in the differentiated state.…”
Section: Irs-1 Maintains Vsmc Differentiationmentioning
confidence: 99%
See 3 more Smart Citations